Functional Analysis of Fructosyl-Amino Acid Oxidases of Aspergillus oryzae - Akazawa, Shin-ichi (American Society for Microbiology, 2004)
Three active fractions of fructosyl-amino acid oxidase (FAOD-Ao1, -Ao2a, and -Ao2b) were isolated from Aspergillus oryzae strain RIB40. N-terminal and internal amino acid sequences of FAOD-Ao2a corresponded to those of FAOD-Ao2b, suggesting that these two isozymes were derived from the same protein. FAOD-Ao1 and -Ao2 were different in substrate specificity and subunit assembly; FAOD-Ao2 was active toward N(ɛ)-fructosyl N(α)-Z-lysine and fructosyl valine (Fru-Val), whereas FAOD-Ao1 was not active toward Fru-Val. The genes encoding the FAOD isozymes (i.e., FAOAo1 and FAOAo2) were cloned by PCR with an FAOD-specific primer set. The deduced amino acid sequences revealed that FAOD-Ao1 was 50% identical to FAOD-Ao2, and each isozyme had a peroxisome-targeting signal-1, indicating their localization in peroxisomes. The genes was expressed in Escherichia coli and rFaoAo2 showed the same characteristics as FAOD-Ao2, whereas rFaoAo1 was not active. FAOAo2 disruptant was obtained by using ptrA as a selective marker. Wild-type strain grew on the medium containing Fru-Val as the sole carbon and nitrogen sources, but strain ΔfaoAo2 did not grow. Addition of glucose or (NH(4))(2)SO(4) to the Fru-Val medium did not affect the assimilation of Fru-Val by wild-type, indicating glucose and ammonium repressions did not occur in the expression of the FAOAo2 gene. Furthermore, conidia of the wild-type strain did not germinate on the medium containing Fru-Val and NaNO(2) as the sole carbon and nitrogen sources, respectively, suggesting that Fru-Val may also repress gene expression of nitrite reductase. These results indicated that FAOD is needed for utilization of fructosyl-amino acids as nitrogen sources in A. oryzae.